Healthcare information security and privacy - Murphy, Sean P. (Sean Patrick), 1968- (New York : McGraw-Hill Education, 2015)
Written by an expert in the field with multiple industry certifications, this definitive resource fully addresses information security and privacy considerations and their implications within the business of patient care. The book begins with an overview of the organization, financing, and delivery of healthcare and discusses technology, terminology, and data management principles. The topic coverage continues across all aspects of information security and privacy, with a special emphasis on real-life scenarios in clinical practices and business operations in healthcare. Learn best practices for healthcare information security and privacy with detailed coverage of essential topics such as information governance, roles and occupations, risk assessment and management, incident response, patient rights, and cybersecurity. Written for a global audience, this comprehensive guide addresses U.S. laws and regulations as well as those within the European Union, the United Kingdom, and Canada.--Publisher description.
Includes bibliographical references and index.
Keywords: Health Information Management -- methods; Health Information Management -- organization & administration; Computer Security; Management Information Systems; Confidentiality; Medical records -- Security measures; Information storage and retrieval systems -- Medical care -- Security measures